NILAI-NILAI KARAKTER DALAM BUKU TEKS SEKOLAH DASAR KELAS RENDAH - Nartani, C. Indah; Adi Nugroho, Irfan (Universitas Sarjanawiyata Tamansiswa, 2022)
The study aims 1) describe character values in low-grade elementary school textbooks; 2) describe the strategy of presenting character values contained in low-grade elementary school textbooks. Expected out of the study are research reports relating to character values in low-grade elementary school textbooks and publications in scientific journals. The research method used is a qualitative descriptive method with the researcher as a key instrument. Data collection is done by the listening-note method. Data analysis is qualitatively descriptive. The object of the research is the textbook of elementary school issued by Kemendikbud and Erlangga. Data analysis includes data reduction, data presentation, data verification, and triangulation. This research cover is a scientific article to be published in nationally accredited scientific journals 3-6 and the proceedings of international seminars. The level of technological maturity (TKT) of this research is included at level 1, which is the basic principle of the techniques studied. The results showed that almost all character grades appeared in low-grade elementary school textbooks. The strategy of presenting character values through reading text and various tasks.